Assessment of photodynamic therapy as a salvage treatment for local failure after chemoradiotherapy or radiotherapy for esophageal cancer in patients aged 80 years or older. Issue 1 (25th September 2022) - Nishikawa, Michiko; Yamamoto, Yoshinobu; Kushida, Saeko; Hirabayashi, Taku; Tanaka, Syunta; Takegawa, Naoki; Mimura, Takuya; Tsumura, Hidetaka; Miki, Ikuya; Tsuda, Masahiro
Abstract: Objectives: Chemoradiotherapy (CRT) or radiotherapy (RT) alone is often the treatment of choice for elderly patients with esophageal cancer with the expectation of organ preservation. However, salvage treatment remains a problem when endoscopic resection is not indicated for local failure after CRT/RT. Photodynamic therapy (PDT) is indicated for local failure after CRT/RT, but there are few reports on its efficacy and safety in elderly patients. This study aimed to assess the outcome of PDT for local failure after CRT/RT for esophageal cancer in elderly patients. Methods: This retrospective single‐center study included 42 patients who first underwent PDT between April 2013 and June 2021. Patients aged ≥80 and <80 years were classified into the elderly and nonelderly groups, respectively. Local complete response rate, overall survival, progression‐free survival, and incidence of adverse events related to PDT were compared retrospectively between the groups. Results: The local complete response rate was 93.3% in the elderly group and 85.7 in the non‐elderly group. The 2‐year overall survival rate was 68.6% and 72.5%, and the 2‐year progression‐free survival rate was 49.5% and 70.0% in the elderly and nonelderly groups, respectively. There was no significant difference in any of these outcomes between the groups. In terms of adverse events, pneumonia and delirium tended to occur more frequently in the elderly group, but there were no serious adverse events in either group. Conclusion: The outcome of salvage PDT in the local control was comparable between the elderly and nonelderly patients for local failure after CRT/RT for esophageal cancer.